Peptides with angiotensin I converting enzyme (ACE) inhibitory activity generated from porcine skeletal muscle proteins by the action of meat-borne Lactobacillus - Castellano, Patricia Haydee (2013)
Angiotensin I-converting enzyme (ACE) inhibitory activity of peptides derived from the hydrolysis of sarcoplasmic and myofibrillar porcine proteins by the action of Lactobacillus sakei CRL1862 and Lactobacillus curvatus CRL705 (whole cells + cell free extracts) was investigated at 30 °C for 36 h. The protein hydrolysates were subjected to RP-HPLC in order to fractionate the extracts for further evaluate the ACE inhibitory activity of the collected peptide fractions. Bioactive fractions were only found from the hydrolysis of sarcoplasmic proteins by both assayed lactic acid bacteria. Identification of peptides contained in these bioactive fractions was carried out by tandem mass spectrometry using a nanoLC-ESI-QTOF instrument and the mascot seach engine. A total of eighteen peptides were characterized from the two most active fractions obtained from the hydrolysis made by L. sakei CRL1862. Regarding L. curvatus CRL705, its proteolytic action was able to generate thirty and twenty peptides, which were identified in the two most active fractions, respectively. It is worth noting that the sequence FISNHAY was generated by the proteolytic action of the two species. Sequence similarity analyses between the peptides identified in this study and those previously identified as ACE inhibitory peptides and detailed in the BIOPEP database were outlined. Results suggest that lactic acid bacteria selected in this study were able to generate peptides with ACE inhibitory activity, thus having potential to be used in the development of functional fermented products.